Intestinal parasitic infections among leukemia patients after chemotherapy and estimation of Interleukin-2 (IL-2) level - Sundus Muayyad Nooruldeen; Abeer Abbas Ali; Azad Mohammed Kamal-Aldin (International Journal of Medical Toxicology and Legal Medicine, 2024)
Background:Intestinal parasites are common cause of infecous disease in leukemia patient receiving anticancer therapy ,additionally , immunosuppresion therapy in such patients may exacerbate the symptoms related to these parasitic infection . Objectives: The current study aimed todetect the prevalence of intestinal parasite infection in leukemia patients after chemotherapy and assess the levels of IL-2 in those patients. Methods:100 stooland serum samples were collected from leukemia patients after receiving chemotherapy from(1-79 years) ages and both sexes. And 25 samples from healthy individuals as a control group. In this cross-sectional study, samples were collected from September 2023 to March 2024 at Kirkuk Oncology and Hematology center. The method used was the direct smear and concentration method (sedimentation by formal ether and flotation by using a saturated salt solution) for the investigation of intestinal parasites and the Sandwich Enzyme-Linked Immunosorbent Assay (Sandwich-ELISA) technique for the determination of level in serum. Results: The results showed that the total infection percentage of intestinal parasites was 28% in leukemia patients. Five species of intestinalparasites were recorded: Entamoeba histolytica (50%), Blastocystis hominis(21.42%), Entrobius vermicularis (14.28%), and (7.14%) patients infected with Giardia lamblia and Ascaris lumbricoides.The percentage of infection infemales was higher than that of males, and higher prevelance of IPI was in (1-9) age group.The statistical analysis showed significantdifferences (P< 0.05) between the percentage of intestinal parasitic infection with age and type of leukemia in leukemia patients, while no significant differences(p>0.05) between the percentage of intestinal parasite and sex. The results showed a significant increase (P< 0.05) in IL-2 in leukemia patients after chemotherapy treatmentinfected with intestinal parasites compared to non-infected patients. Conclusion: The findings of this study indicated that intestinal parasitic infections are still a publichealth problem specially in immunocompromisd leukemia pateints in Kirkuk City, Iraq